(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The evaluation of the curriculum is a critical aspect of curriculum development as it allows the school administration to assess whether the curriculum has successfully achieved its objectives. This study aimed to identify the strengths and areas for improvement in a graduate school curriculum. To conduct this qualitative case study, the researchers utilized purposeful sampling, selecting graduate students in the thesis writing stage and recent graduates from various courses offered in the graduate school. A total of 10 participants willingly participated in the focus group discussion, while four took part in the exit interview. The researchers employed focus group discussions and exit interviews as data collection tools, focusing on the participants’ experiences with the graduate school curriculum. The findings revealed three main themes: Advancing professional capability, empowering experiences, and overcoming research hurdles. These themes indicated that the Graduate School Curriculum had contributed to the development of the participants’ research skills in their respective disciplines, ultimately empowering them to develop leadership skills in the workplace. This was largely facilitated by the professors’ effective facilitation of the learning processes. While this study provides valuable insights into the strengths of the graduate school curriculum, the study points to the need to intensify its scaffolds on the area of research and of reflecting further on the sequence of curricular offerings tailored to fit the context of graduate students in an online environment. A further empirical investigation using quantitative methods is endorsed to obtain more robust information on the curriculum’s best features and to enhance its overall effectiveness.